Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.14
|View full text |Cite
|
Sign up to set email alerts
|

Information-Theoretic Probing with Minimum Description Length

Abstract: To measure how well pretrained representations encode some linguistic property, it is common to use accuracy of a probe, i.e. a classifier trained to predict the property from the representations. Despite widespread adoption of probes, differences in their accuracy fail to adequately reflect differences in representations. For example, they do not substantially favour pretrained representations over randomly initialized ones. Analogously, their accuracy can be similar when probing for genuine linguistic labels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
257
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(265 citation statements)
references
References 31 publications
8
257
0
Order By: Relevance
“…Then, they could be not as readily "available" after finetuning. We explored this hypothesis using Minimum Description Length probes (Voita and Titov, 2020), with the results presented in Appendix B. We found minimal differences across most tasks, where the only significant result was that finetuning on dependency parsing made the corresponding edge probing task easier to learn as a function of the number of examples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, they could be not as readily "available" after finetuning. We explored this hypothesis using Minimum Description Length probes (Voita and Titov, 2020), with the results presented in Appendix B. We found minimal differences across most tasks, where the only significant result was that finetuning on dependency parsing made the corresponding edge probing task easier to learn as a function of the number of examples.…”
Section: Resultsmentioning
confidence: 99%
“…Tenney et al (2019b); ; Peters et al (2018b) introduced task suites that probe for high-level linguistic phenomena such as partof-speech, entity types, and coreference, while Tenney et al (2019a) showed that these phenomena are represented in a hierarchical order within the layers of BERT. Hewitt and Manning (2019) used a geometrically-motivated probe to explore syntactic structures, and Voita and Titov (2020) and Pimentel et al (2020) designed informationtheoretic techniques that can measure the model and data complexity. 1 While probing models depend on labelled data, parallel work has studied the same encoders using unsupervised techniques.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the Transformer decoder has far more parameters than either probe, it is not surprising that less direct representations of some linguistic features would not impact translation performance. Differences in how directly sparse & dense models encode information is an interesting question perhaps well-suited to recent work on minimum description lengths (Voita and Titov, 2020), but we leave it to future study. Meanwhile, the MLP could not rescue sparse model performance on PS-Fxn, PS-Role, and Coref; results were nearly identical as with the linear probe.…”
Section: Are Results Probe-sensitive?mentioning
confidence: 99%
“…Some other work also investigates models' ability to induce syntactic information by measuring accuracy of a probe (Zhang and Bowman, 2018;Hewitt and Manning, 2019;Hewitt and Liang, 2019). However, there is significant uncertainty about how to calibrate such probing results (Voita and Titov, 2020); our model's representations are more directly interpretable and don't require posthoc probing.…”
Section: Analysis: Entity Typing Performancementioning
confidence: 99%